Changes in IGF-I, urinary free cortisol and adipokines during dronabinol therapy in anorexia nervosa: Results from a randomised, controlled trial. Issue 5 (October 2015) - Andries, Alin; Frystyk, Jan; Flyvbjerg, Allan; Støving, René Klinkby
Abstract Objective Anorexia nervosa (AN) is characterised by complex neuroendocrine disturbances due to severe underweight, physical hyperactivity and purging behaviour. Cannabinoid agonists are used to palliate cachexia of various causes, but their interactions with the hormonal systems that are involved in energy metabolism have not been previously described in humans. Therefore we found it of interest to assess interactions between the synthetic cannabinoid agonist dronabinol and insulin-like growth factor I (IGF-I), urinary free cortisol (UFC) and adipokines in patients with chronic AN. Design This was a prospective, double-blind randomised crossover study, conducted at a specialised care centre for eating disorders. The results are based on twenty-four adult women with chronic AN, who completed the study. The participants received dronabinol (oral capsules, 5 mg daily) and matching placebo over four weeks, separated by a four-week washout period. Bioactive IGF was determined by a cell-based bioassay, whereas total IGF-I, IGFBP-2 and -3 and the two adipokines leptin and adiponectines were measured by immunoassays. The UFC excretion was determined by mass spectrometry. Results As previously reported, dronabinol treatment caused a small, yet significant increase in BMI as compared to placebo (+ 0.23 kg/m2; P = 0.04). This modest weight gain predicted a corresponding increase in bioactive IGF-I, while the amount of daily energy expenditure due to physical activity had a comparable but opposite effect. Nevertheless, neither IGF-I, bioactive IGF nor the IGFBPs levels changed significantly during dronabinol intervention as compared to placebo. Adiponectin also remained unaffected by the weight gain, whereas plasma leptin showed a transient increase at three weeks (P < 0.05). UFC levels were decreased during dronabinol intervention. Conclusion Our results showed that low-dosage therapy with the synthetic cannabinoid agonist dronabinol affected neither the concentration nor the activity of the circulating IGF-system in women with severe and chronic AN. However, our results suggest that such treatment may alleviate the increased hypothalamic–pituitary–adrenal axis activity seen in these patients.